2000
DOI: 10.1074/jbc.m908473199
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and tRNA Recognition of Mammalian Mitochondrial Seryl-tRNA Synthetase

Abstract: Animal mitochondrial protein synthesis systems contain two serine tRNAs (tRNAs Ser ) corresponding to the codons AGY and UCN, each possessing an unusual secondary structure; the former lacks the entire D arm, and the latter has a slightly different cloverleaf structure. To elucidate whether these two tRNAs Ser can be recognized by the single animal mitochondrial seryl-tRNA synthetase (mt SerRS), we purified mt SerRS from bovine liver 2400-fold and showed that it can aminoacylate both of them. Specific interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Ser instead of the missing extra arm, because the catalytic core in the C-terminal region is well conserved in mt SerRS (18). Despite low homology in the N-terminal domain between mt SerRS and prokaryotic enzymes, a single, long helical arm was clearly predicted in the N-terminal region of bovine mt SerRS both by the CD spectrum of the recombinant enzyme and computational analysis of the helical structure using the COILS algorithm.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ser instead of the missing extra arm, because the catalytic core in the C-terminal region is well conserved in mt SerRS (18). Despite low homology in the N-terminal domain between mt SerRS and prokaryotic enzymes, a single, long helical arm was clearly predicted in the N-terminal region of bovine mt SerRS both by the CD spectrum of the recombinant enzyme and computational analysis of the helical structure using the COILS algorithm.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, each possesses an unusual secondary structure; tRNA GCU Ser (for codon AGY) lacks the entire D arm (16), whereas tRNA UGA Ser (for codon UCN) has an unusual cloverleaf configuration with an extended anticodon stem (17). We previously demonstrated that the single mt SerRS recognizes these distinct isoacceptors with almost the same activity (18). Additionally, inspection of the primary sequences of several mt SerRSs revealed differences between mammalian mt SerRS and its prokaryotic counterpart in the N-terminal domain responsible for tRNA recognition, which are in line with structural and recognition differences between the extra arms of mammalian mt and prokaryotic tRNAs Ser .…”
mentioning
confidence: 99%
“…It has been suggested that mutations in the S12mt gene result in translational misreading and mitochondrial dysfunction. Recently, we found that the mitochondrial seryl-tRNA synthetase (mt SerRS) gene was located upstream and adjacent to the S12mt gene (57). The genes for S12mt and mt SerRS are considered to be possible candidates for DFNA4.…”
Section: Fig 4-continuedmentioning
confidence: 99%
“…Two tRNA genes that share these characteristics are the isoaccepting leucine tRNA (L CUN , L UUR ) genes. Although these tRNAs have different mRNA codon selectivities (L CUN with anticodon UAG recognizes four codons, CUA, CUG, CUC, and CUU, within mRNA transcripts; L UUR with anticodon UAA recognizes two codons, UUA and UUG), both genes code for tRNAs that accept the same amino acid and both are likely recognized by the same aminoacyl-tRNA synthetase, as shown for isoaccepting serine tRNAs within animal mtDNA (6). Likewise, the identity of these tRNA genes can be switched through a single point mutation in the third base of the anticodon triplet (e.g., TAA to TAG).…”
mentioning
confidence: 99%